Objectively-measured physical activity and stress levels in workers: a systematic review - Marcelo Frio Marins; Barbara Sutil da Silva; Natan Feter; Marcelo Cozzensa da Silva (Revista Brasileira de Atividade Física e Saúde)
To investigate the relationship between objectively measured physical activity and occupational stress in different work environments. This systematic review, registered in the PROSPERO database (CRD42020214884), followed the PRISMA methodology. The search took place in October/2020 in the following databases: Web of Science, SPORTDiscus, MedLine/PubMed, PsycINFO, EMBASE, OVID MEDLINE, Scielo and CINAHL. Keywords related to eligible participants (adults and workers), interventions (physical activity objectively measured), comparison (control group or baseline), outcome (stress), and study design (observational studies) were combined using Boolean terms. From 1,524 identified records, 12 articles were included, totaling 2,082 workers. 66.7% of the studies were carried out in Europe and 50.0% among health professionals. Blue collar workers (20.7% [n = 430]) and white collar workers (18.3% [n = 382]), medical resident (6.5% [n = 135]) and protection services (9.7% [n = 202]) were the predominant occupations. Physical activity was higher in blue-collar workers than in white-collar workers, and shift-working nurses were more active compared to non-shift workers and office workers. Increased mental workload was not associated with time spent on physical activities in most studies (10 [83.3%)]). Some studies showed that light physical activity was associated with higher levels of stress and moderate to vigorous physical activity was beneficial for reducing stress dimensions. In conclusion, most studies did not find an association between objectively measured physical activity and the level of stress in workers. Studies with robust methodologies and covering different groups of workers remain necessary.